Solvent Effects on the Energy Barrier of Excited State Proton Transfer in 3-Hydroxyflavone (Communications in Computational Chemistry, 2018)
The energy barrier of excited state proton transfer (ESPT) process in3-hydroxyflavone (3HF) was studied considering the solvent effects. It was found thatthe ESPT energy barrier increased with the increase of solvent polarity. But the ESPTenergy barrier of 3HF in methanol is lower than in vacuum, n-hexane and acetonitrile.It was found that methanol molecule lowers the ESPT energy barrier by forming aseven-membered-ring 3HF-methanol complex.